Treatment and prevention of delayed onset muscle soreness - Connolly, D. A. J.; Sayers, S. P.; McHugh, M. P. (The Journal of Strength and Conditioning Research, 2003)
Eccentric exercise continues to receive attention as a productive means of exercise. Coupled with this has been the heightened study of the damage that occurs in early stages of exposure to eccentric exercise. This is commonly referred to as delayed onset muscle soreness (DOMS). To date, a sound and consistent treatment for DOMS has not been established. Although multiple practices exist for the treatment of DOMS, few have scientific support. Suggested treatments for DOMS are numerous and include pharmaceuticals, herbal remedies, stretching, massage, nutritional supplements, and many more. DOMS is particularly prevalent in resistance training; hence, this article may be of particular interest to the coach, trainer, or physical therapist to aid in selection of efficient treatments. First, we briefly review eccentric exercise and its characteristics and then proceed to a scientific and systematic overview and evaluation of treatments for DOMS. We have classified treatments into 3 sections, namely, pharmacological, conventional rehabilitation approaches, and a third section that collectively evaluates multiple additional practiced treatments. Literature that addresses most directly the question regarding the effectiveness of a particular treatment has been selected. The reader will note that selected treatments such as anti-inflammatory drugs and antioxidants appear to have a potential in the treatment of DOMS. Other conventional approaches, such as massage, ultrasound, and stretching appear less promising.